Detection of Bacteria Causing Burn Infection Isolated from Several Hospitals in Baghdad - Al-Azzawi , Mundher H.; Alkalifawi, Esam J. Alkalifawi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The results of the present study showed that twenty-five samples were collected for the age group 35–40 years and four samples for the age group 65–70 years for both genders. The results showed that 48 (48%) of the samples were obtained from the hands, 16 (16%) from the legs, 12 (12%) from the abdominal area, and 10 (10%) from the chest area. The four (4%) samples were obtained from burns in the back and thighs area. The samples taken according to the cause of burns were 40 (40%) due to hot water, hot liquids, or hot steam, followed by 18 (18%) due to the use of hot tools, 15 (15%) due to fires, 12 (12%) due to electric currents, 10 (10%) due to chemicals such as strong acids, alkaline lye, paint thinner, or gasoline, and 5 (5%) due to sun ray burns. Sixty pathogenic bacteria were obtained from the burn samples. The number of bacteria isolated from burn wounds was 34 isolates from men and 26 isolates from women. The predominant were 15 (25%) Staphylococcus aureus, 12 (20%) Acinetobacter baumannii, 10 (16.7%) Pseudomonas aeruginosa, 8 (13.3%) Klebsiella pneumoniae, 7 (11.7%) Escherichia coli, 6 (10%) Proteus mirabilis, and 2 (3.3%) Burkholderia cepacia. The antibiotic sensitivity test using the Vitek2 Compact System showed that the resistance rate was recorded in Staphylococcus aureus against Amikacin by 13 isolates, with a rate of 86.6%, and in Acinetobacter baumannii, towards Ceftazidime and Piperacillin antibiotics by 12 isolates at a rate of 100%, and Pseudomonas aeruginosa towards Colistin and Tobramycin at a rate of 6 isolates at a rate of 60%, and Klebsiella pneumoniae towards Colistin and Tobramycin at a rate of 8 isolates at a rate of 100% and Escherichia coli against Amikacin, Colistin, and Imipenem with 7 isolates and 100%, and Proteus mirabilis against Colistin and Tobramycin with 6 isolates and 100%, and Burkholderia cepacia against 8 antibiotics with a rate of 100%. We conclude from the present study that the most susceptible age group to burns is the active age group and that the pathogenic bacteria from burn wounds are mostly resistant to antibiotics.